An English Invention - Crowden, James (Petits Propos Culinaires, 2002)
This piece was first published in Nonesuch, the Bristol University Magazine in Autumn 2000 and is reproduced with their kind permission. It concerns the early days of English cider-making and the claim that the technique of secondary fermentation used in the making of champagne originated in 17th-century England.